Insights into the Synthesis and the Solution Behavior of meso‐Aryloxy‐ and Alkoxy‐Substituted Porphyrins. Issue 25 (28th July 2015) - Birin, Kirill P.; Gorbunova, Yulia G.; Tsivadze, Aslan Yu.; Bessmertnykh‐Lemeune, Alla G.; Guilard, Roger
Abstract: meso ‐RO‐appended (R = alkyl, aryl) porphyrins bearing one or two OR substituents at the tetrapyrrolic macrocycle were synthesized in good yields from 5, 15‐dibromo‐10, 20‐diphenylporphyrins 2H(Br2 DPP), Ni(Br2 DPP) and Zn(Br2 DPP) using an SN Ar reaction. By varying the solvent, the base, the temperature, and the time of the reaction, the optimum conditions were established, and the selective introduction of one or two meso ‐RO substituents at the periphery of the macrocycle was achieved. Moreover, monofunctionalization of Ni(Br2 DPP) according to an SN Ar reaction was used as a key step for the synthesis of rarely explored unsymmetrical porphyrinyl alkyl ethers. 1 H NMR studies of these ethers in CDCl3 revealed concentration‐dependent aggregation of the zinc derivative through coordination of the central metal ion of one molecule to the peripheral oxygen atom of a second tetrapyrrolic macrocycle. Abstract : Synthetic approaches to meso ‐RO‐porphyrins were investigated. Mono‐ and di‐RO‐substituted porphyrins were synthesized from 5, 15‐dibromoporphyrins by using an SN Ar reaction. Furthermore, unsymmetrical porphyrinyl alkyl ethers were prepared from Ni II 5‐bromo‐15‐RO‐porphyrin by using Pd‐catalyzed coupling reactions. Concentration‐dependent aggregation of Zn II meso ‐RO‐porphyrins was studied by NMR spectroscopy.